2001
DOI: 10.1126/science.292.5518.929
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Genomic and Proteomic Analyses of a Systematically Perturbed Metabolic Network

Abstract: We demonstrate an integrated approach to build, test, and refine a model of a cellular pathway, in which perturbations to critical pathway components are analyzed using DNA microarrays, quantitative proteomics, and databases of known physical interactions. Using this approach, we identify 997 messenger RNAs responding to 20 systematic perturbations of the yeast galactose-utilization pathway, provide evidence that approximately 15 of 289 detected proteins are regulated posttranscriptionally, and identify explic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
1,232
6
7

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,807 publications
(1,281 citation statements)
references
References 25 publications
36
1,232
6
7
Order By: Relevance
“…Modeling regulatory circuits [29][30][31] and larger scale networks [32,33], reconstructing metabolic networks [34], investigating network robustness [35,36] and stochastic gene expression in biological systems [37], were among the necessary conditions for a full reemergence of systems biology.…”
Section: Twenty First Century Systems Biologymentioning
confidence: 99%
“…Modeling regulatory circuits [29][30][31] and larger scale networks [32,33], reconstructing metabolic networks [34], investigating network robustness [35,36] and stochastic gene expression in biological systems [37], were among the necessary conditions for a full reemergence of systems biology.…”
Section: Twenty First Century Systems Biologymentioning
confidence: 99%
“…Sophisticated electronic circuit type diagrams of a cell's molecular interactions provide limited insight (15,16). If the cell's protein interrelationships are drawn more like food webs in ecology, we are struck by their similarity (11,17). Food webs are described as "scale-free" networks (18).…”
Section: The Cell's Networkmentioning
confidence: 99%
“…Motifs may coalesce to form modules or subnetworks, which are being unraveled using genomic and proteomic data and, of course, computational methods using graph theory (11,29,(52)(53)(54) (Fig. 1).…”
Section: Modulesmentioning
confidence: 99%
“…Studies comparing mRNA and protein levels typically have shown a weak or poor correlation between them. [1][2][3][4][5] To better determine what actually is happening in a cell, one must know two things: (1) the quantities and activities of the various proteins present at a given time, and (2) the level of critical post-translational modifications that regulate these protein activities. The relative quantitation of mRNA, even on a global scale, cannot provide this information, nor can it describe the dynamics of proteinprotein interactions that may have dramatic effects on protein function.…”
Section: Introductionmentioning
confidence: 99%